Gene silencing by Polycomb complexes - Zhang, Yi (Henry Stewart Talks, 2007)
Discovery of the Polycomb group (PcG) of proteins, Role in embryogenesis, Species conservation, Latest developments in understanding molecular mechanism of gene silencing, Evidence on hierarchical recruitment
Archived at 2015/07/30